Synthesis of Mercaptoethylammonium Chloride in Alkaline Medium - Xiao, Feng; Tan, Shiyu; Zou, Xiaobing (Asian Journal of Chemistry, 2012)
A new way synthesis of mercaptoethylammonium chloride is reported. Using NaOH replace HCl, the results present that the target product can be made in alkaline medium and the velocity of new way is much faster than the tradition one, which is hydrolyzed at high pressure. 1H NMR and IR characterized the structure of the product.